Angioleiomyoma in the ankle mimicking a schwannoma: A case report and review of literature - Junaid Akbar, DPM; Jonathan Gabor, MD; Stuart Katchis, MD (Foot & Ankle Surgery: Techniques, Reports & Cases)
A wide range of differentials arise when a soft tissue mass is encountered. Soft tissue masses of the foot and ankle are difficult to diagnose preoperatively due to delays in presentation and non-specific clinical findings. Further imaging and histological examination are needed for a definitive diagnosis. We present a case of interest of a patient who presented to clinic with a symptomatic solitary mobile mass of the ankle, which initially presented as a schwannoma clinically and on advanced imaging. Histological examination, after surgical excision, confirmed the diagnosis of benign angioleiomyoma. Angioleiomyoma is a rare benign tumor of the tunica media of vasculature smooth muscle. This case report adds to the sparse published literature on angioleiomyomas of the foot and ankle and may aid in the diagnosis of this rare condition.